The role of zakat and waqf institutions in enhancing small and medium enterprises towards the socio-economic development of Muslim countries: leveraging on Malaysia’s potentials - Haneef, Mohamed Aslam; Mohd Ariffin, Noraini; Mohammed, Mustafa Omar (2017)
Zakat and Waqf institutions have played a significant role in the socio-economic development of Muslims throughout Islamic civilization. This role had declined during the colonial period but is now being revived by several contemporary Muslim countries. This research was conducted to study the current practice and propose means to harness the potential of these two institutions and direct them to enhance the socio-economic development of the Ummah via assisting in developing SMEs.